(untitled) - Aaland, Mikkel (San Francisco, 2002)
Photoshop Elements is Adobe's newest image-editing software. Based on the immensely popular, and much more expensive Photoshop, Elements provides low-cost (
Keywords: Photography,Image processing,Nhiếp ảnh,Xử lí ảnh; Digital techniques,Digital techniques,Kỹ thuật số,Kỹ thuật số